Effect of integrated weed management on weed growth, nutrient uptake, economics and energetics in rainfed upland rice (Oryza sativa) - Prasad, K; Rafey, A (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during wet season of 1991 and 1992 at Ranchi, on integrated weed management for weed growth, nutrient uptake, economics and energetics in upland rice (Oryza sativa L.). Integration of pre-emergent butachlor @ 1.5 kg/ha, benthiocarb @ 1.5 kg/ha, oxyfluorfen @ 0.2 kg/ha or oxadiazon@ 0.75 kg/ha with weeding by wheel hoe at 30 days after sowing controlled the weed density and dry weight of weeds in direct-seeded rice. Reduction in nutrient depletion by weeds due to integrated weed management was 44.4 kg N/ha. 10.5 kg P/ha and 20 kg K/ha compared with the weedy control. The application of herbicides alone saved 33. 7 kg N/ha, 4.1 kg P/ha and 14.2 kg K/ha only. The average increase in nutrient uptake by rice was 16.6 kg N/ha, 11.0 kg P/ha and 27.0 kg K/ha with integrated weed management and 10.0 kg N/ha. 6.4 kg P/ha and 14.5 kg K/ha with pre-emergence application of herbicides alone compared with the weedy control. Integrated weed management was comparable with weed-free practice up to 60 days after seeding and hoeing thrice by wheel hoe for grain yield of rice. Combined application of oxadiazon@ 0.75 kg/ha pre-emergence + hoeing at 30 - days after sowing gave the maximum net return (Rs. 2 392/ha), and showed benefit: cost ratio 1.71, energy-use efficiency 7.97 and energy productivity 944 g/mega cal.